Efektivitas Konseling Kelompok Dengan Teknik Assertive Training Dalam Meningkatkan Self Esteem Peserta Didik - Febrianti, Dila; Nikmarijal, Nikmarijal (Program Studi Bimbingan dan Konseling Pendidikan Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Self-esteem is an individual's ability to assess, appreciate, and accept themselves, both in terms of strengths and weaknesses, while recognizing and developing all aspects within themselves. This assessment reflects the attitude of approval or disapproval towards oneself and indicates the extent to which an individual believes they are capable, valuable, successful, and worthy. Low self-esteem can make it difficult for students to evaluate and assess themselves. This issue is observed among some 10th-grade students at SMA Negeri 2 Sungaiselan, where students exhibit low confidence, such as being afraid or shy to express opinions, having difficulty refusing requests, and struggling to say